SEMI-QUANTITATIVE ANALYSIS OF SARS-COV-2 IGG ANTIBODIES FOLLOWING CHADOX1-NCOV (COVISHIELD™) VACCINATION - KUMAR M, RAVISH; DODDAMANI, PRAVEEN KUMAR; KISHANRAO, NAGARKAR RAJHANS; K, PARANDEKAR PRASHANT; M, JISHA; NARAYANA, MARAPPA; MAHADEVAIAH, PRATHIBA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The objectives of this study were semi-quantitatively analyze SARS-COV-2 IgG antibodies following covishield vaccination in healthcare workers and to follow-up them for 6 months for persistence of antibodies and for getting infected with SARS-COV-2. Methods: This was a prospective cohort study which was conducted at tertiary care hospital, South India. The blood samples were collected after second dose of vaccine at 28 days, 60 days, and 120 days. The serum was subjected for detection of IgG antibodies against S1 RBD (Receptor binding domain) of the spike protein antigen by Euroimmun kit (PerkinElmer company, Germany) using ELISA. Results: Out of 30 healthcare workers, 28 (93.3%) were seropositive and 2 (6.7%) were seronegative. Out of two seronegative, one participant acquired SARS-COV-2 infection with severe symptoms. There was approximately 50% reduction in antibody levels in almost all seropositive individuals after 3 months of second dose. Even after 6 months, 25 (83.3%) were seropositive, 2 (6.7%) were seronegative, and 3 (10%) were borderline. When the IgG antibody ratio levels of 28 days following second dose of vaccination were compared with levels after 6 months, which showed, p value of 0.024 which is <0.05 implies statistically significant. Conclusion: Covishield vaccine induced good immune response in majority of the participants, the levels were sustainably positive until 6 months but decreasing pattern. The vaccine-induced antibodies prevented the severe symptoms among vaccine breakthrough infections.